# .

# Schur's inequality

In mathematics, Schur's inequality, named after Issai Schur, establishes that for all non-negative real numbers x, y, z and a positive number t,

\( x^t (x-y)(x-z) + y^t (y-z)(y-x) + z^t (z-x)(z-y) \ge 0 \)

with equality if and only if x = y = z or two of them are equal and the other is zero. When t is an even positive integer, the inequality holds for all real numbers x, y and z.

When t=1, the following well-known special case can be derived:

\( x^3 + y^3 + z^3 + 3xyz \geq xy(x+y) + xz(x+z) + yz(y+z) \)

Proof

Since the inequality is symmetric in x,y,z we may assume without loss of generality that \( x \geq y \geq z \). Then the inequality

\( (x-y)[x^t(x-z)-y^t(y-z)]+z^t(x-z)(y-z) \geq 0\, \)

clearly holds, since every term on the left-hand side of the equation is non-negative. This rearranges to Schur's inequality.

Extension

A generalization of Schur's inequality is the following: Suppose a,b,c are positive real numbers. If the triples (a,b,c) and (x,y,z) are similarly sorted, then the following inequality holds:

\( a (x-y)(x-z) + b (y-z)(y-x) + c (z-x)(z-y) \ge 0. \)

In 2007, Romanian mathematician Valentin Vornicu showed that a yet further generalized form of Schur's inequality holds:

Consider \( a,b,c,x,y,z \in \mathbb{R} \), where \( a \geq b \geq c \), and either \( x \geq y \geq z \) or \( z \geq y \geq x \). Let \( k \in \mathbb{Z}^{+} \), and let \( f:\mathbb{R} \rightarrow \mathbb{R}_{0}^{+} \) be either convex or monotonic. Then,

\( {f(x)(a-b)^k(a-c)^k+f(y)(b-a)^k(b-c)^k+f(z)(c-a)^k(c-b)^k \geq 0}.\, \)

The standard form of Schur's is the case of this inequality where x = a, y = b, z = c, k = 1, ƒ(m) = mr.[1]

Notes

^ Vornicu, Valentin; Olimpiada de Matematica... de la provocare la experienta; GIL Publishing House; Zalau, Romania.

Retrieved from "http://en.wikipedia.org/"

All text is available under the terms of the GNU Free Documentation License